2018
DOI: 10.1063/1.5054108
|View full text |Cite
|
Sign up to set email alerts
|

Determination of modified figure of merit validity for thermoelectric thin films with heat transfer model: Case of CuCrO2:Mg deposited on fused silica

Abstract: Thermoelectric performance of a material is determined using a figure of merit (FOM) determined as ZT (ZT = σS2T/κ where σ is the electrical conductivity, S is the Seebeck coefficient, κ is the thermal conductivity, and T is the temperature). In the case of a thin film, it is normal in the first approach to consider calculating the FOM by using the thermal conductivity of the film. However, both the thermal influence of the substrate and the emissivity of the film must also be taken into account. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Sinnarasa et al 55 , an effective can be calculated for the stabilized -CuI: Z'T = 0.02 at 100 °C. This value is 2.6 Z'T =  S² s T time larger than previously reported p-type Mg doped CuCrO 2 thin film at the same temperature 55 .…”
Section: Thermoelectric Properties Of Stabilized -Cuimentioning
confidence: 99%
See 1 more Smart Citation
“…Sinnarasa et al 55 , an effective can be calculated for the stabilized -CuI: Z'T = 0.02 at 100 °C. This value is 2.6 Z'T =  S² s T time larger than previously reported p-type Mg doped CuCrO 2 thin film at the same temperature 55 .…”
Section: Thermoelectric Properties Of Stabilized -Cuimentioning
confidence: 99%
“…Sinnarasa et al 55 , an effective can be calculated for the stabilized -CuI: Z'T = 0.02 at 100 °C. This value is 2.6 Z'T =  S² s T time larger than previously reported p-type Mg doped CuCrO 2 thin film at the same temperature 55 . The carrier density (10 19 cm -3 ), the large Seebeck coefficient and the Z'T from this work are clearly adapted for thermoelectric applications 56 .…”
Section: Thermoelectric Properties Of Stabilized -Cuimentioning
confidence: 99%
“…In general, the thin lms maintained the high Seebeck coefficient values reported for copper oxides 3,35,45,[61][62][63][64][65] (see Table 1), comparing favourably with other common thermoelectric materials such as Bi 2 Te 3 , 66 PbTe, 67 and CuAlO 2 , 68 and advanced materials such as Ca 3Àx Bi x Co 4 O 9+d , 69 oxides, 62,63 and borides, 64,65 which makes them ideal for sensing applications. Interestingly, a correlation can be observed in Table 1 between the Seebeck coefficient of the lms and their electrical resistance: the lm with the highest conductivity (CuO:O) also possesses the highest Seebeck coefficient.…”
Section: Thermoelectric Studiesmentioning
confidence: 68%
“…It can be explained by the effects of micro and nano structuration which cause a decrease of the thermal conductivity compared to the same bulk materials. Moreover, as described by Sinnarasa et al [41], the impact of ther mal conductivity of the film can be neglected in comparison with the thermal conductivity of the substrate. In our case, the fused silica has a very low thermal conductivity (1.38 W m À1 K À1 at 300K) [56].…”
Section: Thennal Conductivitymentioning
confidence: 99%
“…Temperature sensors based on Seebeck effect require also a low thermal conductivity and low material quantity to avoid thermal pumping. In previous work [41], we have demonstrated that in the case of thin films, the thermoelectric material can be considered as a composite made with the substrate and the thin film. The sub strate does not participate to the electrical conduction and the Seebeck effect but it definitely influences the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%